Examining the determinants of commercial banks’ profitability in fertile crescent countries - Salem, Salem Mohammad Abdelaziz (2020)
There are a large number of studies examining the determinants of bank profitability, either at the country level or even at the cross-country level. However, an area that has not been adequately explored is the impact of the political instability on banking systems. Political instability has a detrimental effect on economic, financial and political systems. In addition, research on the profitability of banks in the Fertile Crescent Countries (FCC) is very limited despite being one of the key global banking markets and an unstable area as well. Hence, this study provides a new insight on bank profitability using political risk indicators. Using system generalized method of moment dynamic model estimation; this study examines the effect of political risk, bank-specific, industry-specific, and macroeconomic factors on the profitability of banks in FCC region over the period of 1996-2018. The results show that there is a significant direct impact of political risk on bank profitability. It also finds that the bank-specific factors, industry-specific, and macroeconomic factors are significant determinants of bank profitability in FCC region. In terms of theories, the study finds evidence to support the political risk theory and resource-based theory, while it finds no evidence to support the structure conduct performance theory. The results are also robust when controlling the global financial crisis and when using panel data techniques. The findings of this study have major policy implications. FCC authorities need to counteract the negative impact of political risk by increasing supervision, improving the quality of current banking activities, mitigating the problem of non-performing loans, and avoiding the negative impact of macroeconomic conditions. FCC banks also need to track policy changes because these changes affect their profitability. Moreover, local banks should be encouraged to invest in safe-haven international financial markets to mitigate risk